Impactos da formação inicial no curso de pedagogia PARFOR UFPA nas práticas curriculares de docentes do ensino fundamental - RABELO, Mayara Andreza Lago Melo (2021)
The present work brings research results impacts of the initial formation in the curricular practices of teachers of the Elementary School of the state of Pará in formation at PARFOR / UFPA, carried out within the scope of the UFPA Pedagogy course, Bragança campus. The objective is to analyze whether the curricular practices of teachers in elementary school are undergoing changes due to the initial training received. This is a three-year longitudinal qualitative research that investigated a group of 52 teachers from UFPA classes at the Bragança, Augusto Correa and Tracuateua centers, northeastern Pará. Data were collected at three different moments of academic life. and professional teachers, from 2017 to 2019. Were used as instruments of collection of memorial data of teacher education, questionnaire and interview. The results show that the teachers had permanence in their practices regarding the references they use to select the contents, in the organization of the class for the activities, in addition to the assessment tools and we noticed that there were changes in the choice of curriculum materials and the organization of the subjects. teaching content, initial education contributed to make them more critical and reflective, establishing more interactive relationships with students, building new planning and teaching strategies, considering the needs and contexts of acting schools.